Exercise for sport-related concussion and persistent postconcussive symptoms - Nadir Haider, M.; Bezherano, I.; Wertheimer, A.; Siddiqui, A. H.; Horn, E. C.; Willer, B. S.; Leddy, J. J. (Sports Health: A Multidisciplinary Approach, 2021)
Context: Emerging research supports the use of mild to moderate aerobic exercise for treating sport-related concussion (SRC) and persistent postconcussive symptoms (PPCS), yet the current standard of care remains to be strict rest. The purpose of this review is to summarize the existing literature on physical activity and prescribed exercise for SRC and PPCS. Evidence Acquisition: PubMed and Embase were searched in April of 2019 for studies assessing rest or prescribed exercise for SRC and PPCS. No specific search syntax was used. Study Design: Clinical review. Level of Evidence: Level 4. Results: A majority of studies show that spontaneous physical activity is safe after SRC and that subsymptom threshold aerobic exercise safely speeds up recovery after SRC and reduces symptoms in those with PPCS. Exercise tolerance can safely be assessed using graded exertion test protocols within days of injury, and the degree of early exercise tolerance has diagnostic and prognostic value. Conclusion: Subsymptom threshold aerobic exercise is safe and effective for the treatment of SRC as well as in athletes with PPCS. Further research is warranted to establish the most effective method and dose of aerobic exercise for the active treatment of SRC and whether early exercise treatment can prevent PPCS in athletes.